2002
DOI: 10.1590/s1516-44462002000200011
|View full text |Cite
|
Sign up to set email alerts
|

Aspectos genéticos e sociais da sexualidade em pessoas com síndrome de Down

Abstract: As representações que pais e educadores fazem da sexualidade de pessoas com a síndrome de Down (SD) referem, muitas vezes, a atitudes agressivas ou, então, condutas assexuadas, exclusivamente fundamentadas na afetividade. Este trabalho faz uma análise da literatura referente à sexualidade e à reprodução em portadores dessa síndrome e avalia as possibilidades de recorrência do distúrbio a partir da segregação cromossômica em portadores de diferentes tipos de trissomia 21. Diversas publicações mostram a existênc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0
10

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 19 publications
0
3
0
10
Order By: Relevance
“…Comparing the data available from the middle of the last century, it is possible to perceive the increase in the life expectancy of this population [5]. Based on the studies of Moreira and Gusmão [6], DS is characterized by a variable degree of delay in mental and motor development. In the case of child development, it is observed that children with DS exhibit delay in the development of motor skills, indicating that this milestone appears at a different time when compared to children with normal development [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Comparing the data available from the middle of the last century, it is possible to perceive the increase in the life expectancy of this population [5]. Based on the studies of Moreira and Gusmão [6], DS is characterized by a variable degree of delay in mental and motor development. In the case of child development, it is observed that children with DS exhibit delay in the development of motor skills, indicating that this milestone appears at a different time when compared to children with normal development [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…1 The incidence in the USA is one out of every 700 births, and it is estimated that at least 100 thousand individuals in Brazil are diagnosed with the syndrome. [2][3][4] Structural and functional abnormalities are found in the nervous system of children with DS. Diffuse brain damage and peculiar electrical functioning during cognitive development result in poor analysis, synthesis and speech skills.…”
Section: Introductionmentioning
confidence: 99%
“…Down syndrome (DS), or trisomy 21, is the most common chromosome abnormality in humans, with a prevalence of 1 in every 700 births in South America (Moreira & Gusmao, ). It is clinically characterized by a broad spectrum of abnormalities (Kanamori, Witter, Brown, & Williams‐Smith, ; Malt et al, ; Soares, Calheiros, & Neto, ), that include hearing changes.…”
Section: Introductionmentioning
confidence: 99%